Provesi SDM Maritim Perikanan Tangkap - Firdayanti J. Umar; Muhammad Nawir; Nurfadilah Syawal Ibraya (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
Indonesia as an archipelagic country has very high resources in the fisheries and marine sectors, where these resources become weapons in improving the welfare of the people in particular and become capital in national development patterns. However, poverty is still an icon for fishermen. The income of fishing fishermen can be said to be different from other types of business because the fishing business is uncertain, where the income fluctuates and speculates, which can lead to the growth of poverty. The aim to be achieved in this research is to reveal and analyze things that influence the income of capture fisheries fishermen. Meanwhile, the author took the explanatory descriptive method as the research method. Data collection came from 100 fishermen respondents with discussion of fishermen's profiles in the form of age, education, family responsibilities, experience and length of time at sea.